Making it real: Exploring transdisciplinary curriculum at dubai women’s college - Saudelli , Mary Gene (Journal of Interdisciplinary Studies in Education, 2014)
This paper describes a case study of the design and implementation of a transdisciplinary curriculum design (Drake, 2007) at Dubai Women’s College through the lens of transformative learning theory (Mezirow, 2000). Data were collected during the 2008-2009 academic year from 19 participant educators and supervisors and consisted of three interviews and textual data in the form of: lesson plans, syllabi, curriculum project documents, assessments, strategic plans, and field notes. The following themes are discussed and related to transformative learning theory in context: (a) aspects of life and change for Emirati female students, (b) the transdisciplinary curriculum company visit, (b) the transdisciplinary curriculum bazaar, (c) the transdisciplinary curriculum current issues forum, (d) Emirati identity and empowerment, and (e) Emiratization – the overriding goal. Findings reveal the nature of transformative learning in this Arab context during a period of globalization and change.